Thu nhận xenlulozơ từ bã mía cho sản xuất etanol sinh học theo phương pháp xử lý với axit axetic - Diễn, Lê Quang; Anh, Phạm Tuấn; Anh, Tô Kim; Minh Nguyệt, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
Sugarcane bagasse contains more than 40 % of cellulose; this material presents a potential feedstock for bioethanol production. In this study, the two-stage treatment of bagasse was used for preparation of cellulosic pulp. Firstly, sugarcane bagasse was treated by mixture of acetic acid and hydrochloric acid (99/1 v/v) in conditions of liquor-tobagasse ratio (10:1) l/kg, temperature (80-90 oC) and 60-90 mins of cooking. Secondary, pretreated bagasse was submerged in sodium hydroxide solution (0.75-1.0 % w/w), at temparature of 80-90 oC, for 30 mins. The yield of cellulosic pulp, which presents 80-85 % purity, was 51-53% of over dry bagasse. Enzymatic saccharification of pretreated bagasse by Novozymes commercial enzyme Cellic®CTec2 with dosage of 45 FPU/g of pretreatred bagasse achieved the reduce sugar yield an average 36.2-38.0 % of over dry bagasse. Fermentation of sugars has been succesful. Study on chemical recovery showed that at laboratory conditions more than 75 % of consumed acetic acid and hydrochloric acid can be recovered by vacuum distillation and can be reused for obtaining of cellulose.